DETECTION & DIFFERENTIATION OF SOFT TISSUE INJURIES IN ADVANCE MAGNETIC RESONANCE IMAGING (MRI) - Muhammad Qaisar Pervaiz; Ayesha Younas; Altaf Pervez Qasim (Journal of University Medical & Dental College, 2015)
ABSTRACT BACKGROUND: Radiology is the application of the science of diagnostic imaging to questions of clinical and medicolegal practice. Forensic medicine refers to the application of medical knowledge in the collection of medical evidence to be used by law enforcing agencies & in courts of law for furthering of justice. Such evidence may be collected from either living or deceased subjects. Modern techniques & Imaging modalities such as computed tomography (CT) and Magnetic Resonance Imaging (MRI) are being used for assessment of soft tissue trauma, morphology of organ or joint as well as wounds and their complications. The ongoing development of imaging and the recent integration of cross-sectional imaging methods into the medicolegal workﬂow have resulted in an increasing number of forensic institutes acquiring dedicated CT and MRI scanners. METHODOLOGY: Out of the total three Medico legal cases studied in Radiology Department of Sir Ganga Ram Hospital Lahore; two were ultimately proven to have hidden ﬁndings. All the three cases presented with non-speciﬁc injury during ﬁght on head and appeared in front of medical board for examination regarding depth of scar underlying head injury. Final diagnosis was achieved by MRI speciﬁc sequences. RESULTS: Initial examiner found no fracture on digital X-rays of skull AP & Lat. Views in all three ndcases. On MRI, one case was normal. In the 2 case, signiﬁcant soft tissue injuries were identiﬁed in rdthe eye ball i.e. subluxation of lens in right eye and in 3 case, sub-galleal bone deep hematoma was identiﬁed on left temporal area (corresponding to the injury). CONCLUSION: Magnetic Resonance Imaging is shown to have best modality to identify hidden ﬁndings & is one of the increasingly used modality in the collection of forensic evidence. The expertise of radiology and forensic medicine should be integrated to settle the quarries of detection and differentiation of soft tissues trauma in many cases of clinical as well as forensic interest.